The Potential Use of Algae as Biosorbents for Mercury Removal in the Indonesian Water Bodies - Josefano, Richelle Bertly; Belva, Felicia Lael; Yoel, Abigail; Rahardja, Richelle Tirta; Dharmawan, Nethania Angeline; Tjandra, Noah William; Bani, Mario Donald (Indonesia International Institute for Life Sciences, 2023)
Contamination of mercury in the water body in Indonesia has become a big concern for many people due to the harmful effects of this heavy metal when it enters the body. Mercury contamination may cause neurological disorders that lead to loss of senses, and damage the brain, the central nervous system, the kidney, and can lead to birth defects. Human activities, such as Coal-Fired Power Plants (CFFPs) and Artisanal and Small-Scale Gold Mining (ASGM) as well as other mining activities, are among the biggest contributors of mercury emissions in Indonesia’s water body. Biosorbents such as fungi, bacteria and algae can be utilized to alleviate this problem, with algae being the most reliable biosorbent due to its abundance in Indonesia, low cost manufacturing, and high metal ion binding capacity. There are three varieties of algae that can be used as a mercury biosorbent: green algae (Chlorophyta), red algae (Rhodophyta), and brown algae (Phaeophyta). Different studies have shown that the most compatible mercury biosorbent is green algae due to its highest mercury absorption capacity. However, there are limited studies about the use of algae in Indonesia as mercury biosorbent.